(untitled) (Revista Investigación & praxis en CS Sociales, 2022)
This article aims to analyze the history, contributions, uses, and discussions that psychoanalysis has sparked in Colombia through a documentary analysis to promote visibility, recognition, and application of this psychological approach in the healthcare system. This study is based on the qualitative approach of documentary review and has a descriptive scope, addressing four categories of analysis: history, contributions, uses, and discussions. The results obtained led to the conclusion that, regarding history, the theoretical corpus of the approach reached the national territory 30 years after its beginnings in Austria-Vienna; concerning uses, various non-clinical scenarios were found where its conceptual and practical elements are relevant; regarding contributions, socio-legal, cultural, and health aspects were analyzed; and concerning discussions, psychoanalytic practices sparked a variety of criticisms from popular opinion and transdisciplinarity, based on misconceptions about its method.